2012
DOI: 10.1080/03075079.2012.709489
|View full text |Cite
|
Sign up to set email alerts
|

Intentionality and developing researcher competence on a UK master's course: an ecological perspective on research education

Abstract: This paper presents an ecological perspective on the developing researcher competence of participants in the research education component of a professionally oriented master's course. There is a particular focus on the intentionality (as in 'purpose') of the participants' research education activity. The data used to develop the ecological perspective, and which at the same time is interpreted from this ecological perspective, consists of interactive, reflective and more product-like written outputs generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…While there are strengths to this approach, construction of individual roles can be neglected (Lee, 2008;Stelma & Fay, 2012). This is problematic because there is more to being a researcher than just 'doing research'.…”
Section: Functionalist Approaches To Research Trainingmentioning
confidence: 99%
“…While there are strengths to this approach, construction of individual roles can be neglected (Lee, 2008;Stelma & Fay, 2012). This is problematic because there is more to being a researcher than just 'doing research'.…”
Section: Functionalist Approaches To Research Trainingmentioning
confidence: 99%
“…According to Stelma and Fay (2014) In order to investigate the KAU/ELI teachers' perceptions, expectations and change of practice related to the ecology of the KAU/ELI teaching context it was found that the most applicable way was to ask those teachers questions and to analyze their answers. Indeed, surveys are considered the most frequently employed descriptive method used in educational research (Cohen and Manion, 1985).…”
Section: An Ecological Perspective Supporting the Effect Of Expectatimentioning
confidence: 99%
“…1-2) which have the power to redirect the agents" attitudes and practices. Stelma and Fay (2014) intentionality paradigm related to directing the deliberate activity of individuals towards certain directions in response to the expectations of the context offers a confirmation to Tudor (2003) and an explanation to the change of practice of our interviewees, let alone their conviction of making the right choice by conforming to what the context expects regardless of their recognized beliefs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, researchers need to consider all these possibilities and complexities. Having done so, they can make informed decisions and demonstrate what we term "researcher purposefulness" (or more technically, "researcher intentionality", see Stelma & Fay, 2014;Stelma, Fay & Zhou, 2013) in their RM-ly practice.…”
Section: Introductionmentioning
confidence: 99%